An O‐methyltransferase modifies accumulation of methylated anthocyanins in seedlings of tomato. (15th October 2014) - Gomez Roldan, Maria Victoria; Outchkourov, Nikolay; van Houwelingen, Adèle; Lammers, Michiel; Romero de la Fuente, Irene; Ziklo, Noa; Aharoni, Asaph; Hall, Robert D.; Beekwilder, Jules
Summary Anthocyanins contribute to the appearance of fruit by conferring to them a red, blue or purple colour. In a food context, they have also been suggested to promote consumer health. In purple tomato tissues, such as hypocotyls, stems and purple fruits, various anthocyanins accumulate. These molecules have characteristic patterns of modification, including hydroxylations, methylations, glycosylations and acylations. The genetic basis for many of these modifications has not been fully elucidated, and nor has their role in the functioning of anthocyanins. In this paper, AnthOMT, an O‐methyltransferase (OMT) mediating the methylation of anthocyanins, has been identified and functionally characterized using a combined metabolomics and transcriptomics approach. Gene candidates were selected from the draft tomato genome, and their expression was subsequently monitored in a tomato seedling system comprising three tissues and involving several time points. In addition, we also followed gene expression in wild‐type red and purple transgenic tomato fruits expressing Rosea1 and Delila transcription factors. Of the 57 candidates identified, only a single OMT gene showed patterns strongly correlating with both accumulation of anthocyanins and expression of anthocyanin biosynthesis genes. This candidate (AnthOMT) was compared to a closely related caffeoyl CoA OMT by recombinant expression in Escherichia coli, and then tested for substrate specificity. AnthOMT showed a strong affinity for glycosylated anthocyanins, while other flavonoid glycosides and aglycones were much less preferred. Gene silencing experiments with AnthOMT resulted in reduced levels of the predominant methylated anthocyanins. This confirms the role of this enzyme in the diversification of tomato anthocyanins.